Acute toxicity of sea-dumped chemical munitions: luminating the environmental toxicity of legacy compounds*. Issue 1 (1st January 2016) - Mohammed Abdullah Christensen, Ilias; Swayne Storgaard, Morten; Fauser, Patrik; Foss Hansen, Steffen; Baatrup, Erik; Sanderson, Hans
Abstract: As a result of the disarmament of Germany after the Second World War, 65, 000 tons of chemical munitions were dumped in the Baltic Sea. Approximately 13, 000 tons containing chemical warfare agents (CWAs) of which 11, 000 tons were dumped in the Bornholm Basin east of Bornholm. This paper addresses the ecotoxicity of compounds actually present in the Bornholm dumpsite by obtaining novel acute ecotoxicity data. EC50 values were successfully obtained for 12 CWAs from acute tests using Allivibrio fischeri (Microtox™). The three most toxic compounds were α-chloroacetophenone, 2-chlorovinylarsonic acid and 1, 2, 5-trithiepane having EC50 values of 11.20, 31.20 and 1170 μg L −1, respectively. A. fischeri demonstrated hormesis when exposed to triphenylarsine and triphenylarsine oxide at concentrations of 100 and 50 mg L −1, respectively. Four different mixtures were assessed including compounds which were dissolvable; a mixture of sulphur mustard degradation products, a mixture of the three most toxic sulphur mustard compounds, a mixture of organoarsenical degradation products and a mixture of all compounds. The mixtures deviate by a factor of 1.5–2.5 from the prediction of the concentration addition model and hence, the mixtures demonstrate no sign of synergism or antagonism. The compounds presented in this study are mainly CWA.